Pendidikan Islam di Era Global dengan Menjaga Nilai, Merangkul Perubahan - Miftahul Husnah; Misra Misra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Globalization as an unavoidable global phenomenon has brought significant impacts in various sectors of life, including education. In the context of Islamic education, globalization offers opportunities to access information and exchange knowledge more widely, as well as encourage the development of innovative educational technology. However, the flow of globalization also contains challenges in the form of the entry of foreign cultural influences that can threaten the sustainability of local values, including Islamic values. Therefore, Islamic education in the global era is required to maintain the integrity of the fundamental values ​​of Islam, while being able to adapt to the development of the times. This article examines how Islamic education can respond to global changes without losing its essence, with a critical, selective, and constructive approach. This study aims to provide insight into strategies that can be taken to ensure that Islamic education remains relevant and firmly rooted in Islamic values.